Dynamics of the Transcriptome and Accessible Chromatin Landscapes During Early Goose Ovarian Development - Hu, Shenqiang; Yang, Shuang; Lu, Yao; Deng, Yan; Li, Li; Zhu, Jiaran; Zhang, Yuan; Hu, Bo; Hu, Jiwei; Xia, Lu; He, Hua; Han, Chunchun; et al. (Frontiers in Cell and Developmental Biology, 2020)
In contrast to the situation in mammals, very little is known about the molecular mechanisms regulating early avian ovarian development. This study aimed to investigate the dynamic changes in the histomorphology as well as the genome-wide transcriptome and chromatin accessibility landscapes of the goose ovary during late embryonic and early post-hatching stages. Results from haematoxylin-eosin-, periodic acid-Schiff-, and anti-CVH immunohistochemical stainings demonstrated that programmed oocyte loss, oocyte nest breakdown and primordial follicle formation, and the primordial to secondary follicle transition occur during the periods from embryonic day 15 (E15) to post-hatching day 0 (P0), from P0 to P4, and from P4 to P28, respectively. RNA-seq and ATAC-seq analyses revealed dynamic changes in both the ovarian transcriptome and accessible chromatin landscapes during early ovarian development, exhibiting the most extensive changes during peri-hatching oocyte loss, and moreover, differences were also identified in the genomic distribution of the differential ATAC-seq peaks between different developmental stages, suggesting that chromatin-level regulation of gene expression is facilitated by modulating the accessibility of different functional genomic regions to transcription factors. Motif analysis of developmental stage-selective peak regions identified hundreds of potential cis-regulatory elements that contain binding sites for many transcription factors, including SF1, NR5A2, ESRRβ, NF1, and THRβ, as well as members of the GATA, SMAD, and LHX families, whose expression fluctuated throughout early goose ovarian development. Integrated ATAC-seq and RNA-seq analysis suggested that the number and genomic distribution of the newly-appeared and disappeared peaks differed according to developmental stage, and in combination with qRT-PCR validation potentiated the critical actions of the DEGs enriched in cell cycle, MAPK signaling, and FoxO signaling pathways during peri-hatching oocyte loss and those in ligand-receptor interaction, tissue remodeling, lipid metabolism, and Wnt signaling during primordial follicle formation and development. In conclusion, our study provides a framework for understanding the transcriptome and accessible chromatin dynamics during early avian ovarian development and a new avenue to unravel the transcriptional regulatory mechanisms that facilitate the occurrence of relevant molecular events.